Adaptive learning in changing environments - Rocha, Miguel (2003)
The remarkable adaptation of living creatures to their environments comes as a result of the interaction of two orthogonal processes: evolution and learning. Within the Machine Learning arena, both mechanisms inspired the development of the Evolutionary and Connectionist Computation fields, which can be combined under two different views, the Lamarckian and Baldwinian approaches. Comparative tests reward the latter when changing environments are considered.